Implementasi Etnomatematika pada Materi Kesebangunan dan Kekongruenan dengan Rumah Adat Karo - Kudadiri, Natalia Rama; Siallagan, Yesica; Siahaan, Tryona Loise; Mailani, Elvi; Saragih, Doni Irawan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article discusses the Karo traditional house, a review from Etnomathematics. Karo is located in North Sumatra and has high value history, culture and artifacts. One of these artifacts that still survives is the Karo traditional house. This traditional house not only functions as a protector for its residents but also has a deep function and meaning in accordance with the customs and culture of the community. In Karo traditional houses, the form, function and motifs of the aesthetic elements depict the close relationship between humans and their natural environment. Examining the aesthetic elements of Karo traditional houses which contain geometric concepts. Without studying geometric concepts in mathematics, Karo people have applied geometric concepts in everyday life, reflected in creating aesthetic elements in Karo traditional houses. The method used is literature study